Enhancing the Aroma of Dealcoholized La Mancha Tempranillo Rosé Wines with Their Aromatic Distillates - M. Osorio Alises; E. Sánchez-Palomo; M. A. González Viñas (Beverages, 2024)
The increasing demand for non-alcoholic beverages has led to the development of dealcoholized wines. However, current dealcoholization techniques often negatively impact wine aroma due to the loss of volatile compounds. This study investigates the impact of incorporating an aromatic distillate, collected during the spinning cone column (SCC) dealcoholization process, back into dealcoholized Tempranillo rosé wines. The aromatic distillate was added to dealcoholized wine in varying concentrations (0.5%, 1.0%, and 1.5% v/v). A total of 57 volatile compounds, including 25 varietal and 32 fermentative compounds, were identified and quantified using gas chromatography–mass spectrometry (GC-MS). The addition of the aromatic distillate significantly increased the concentration of several volatile compounds, notably C6 compounds, terpenes, benzene compounds, and esters. The odor activity values (OAVs) reveal that increasing distillate concentrations led to a higher number of compounds with OAVs greater than 1, indicating enhanced individual aroma contributions. The fruity and sweet aromatic series were predominant in all samples, with their total intensity increasing with higher distillate concentrations. However, the addition of 1.5% v/v of the aromatic distillate (AW3) resulted in an alcohol content exceeding the legal limit for dealcoholized wine, classifying it as a reduced-alcohol wine. The study concludes that adding 1% v/v of the aromatic distillate to dealcoholized Tempranillo rosé wine effectively enhances the aroma profile while remaining within regulatory limits for dealcoholized wine. This approach presents a viable method for producing high-quality, aromatic, dealcoholized wines that meet consumer demand for non-alcoholic beverages.